2019
DOI: 10.1097/acm.0000000000002543
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Individual Mentored Career Development (K) Awards on the Research Trajectories of Early-Career Scientists

Abstract: Purpose This analysis examined the role of a National Institutes of Health (NIH) individual Mentored Career Development Award (K01, K08, K23) on launching and sustaining independent research careers for early-career scientists, and investigated the effects of these awards during and after the doubling of the NIH budget. Method The authors used grants data from the NIH covering the period 1990 through 2016, and compared success in receipt of R01 equivale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 15 publications
3
45
0
Order By: Relevance
“…Immigrant scientists make up roughly two-thirds of the postdoc workforce and 15 to 25 percent of the FTR01 awardee pool is foreign born [12,24] If the number of FTR01 awardees in a given year is adjusted to omit those who were ineligible for a training award, roughly half of the remaining FTR01 awardees received a training award before their R01 in 2017. Furthermore, the percentage of training awards among the FTR01 awardee population is overrepresented relative to the percentage of training awards among the postdoc population, supporting previous results indicating training awards confer a competitive advantage in attempts to land a faculty position [12,14].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Immigrant scientists make up roughly two-thirds of the postdoc workforce and 15 to 25 percent of the FTR01 awardee pool is foreign born [12,24] If the number of FTR01 awardees in a given year is adjusted to omit those who were ineligible for a training award, roughly half of the remaining FTR01 awardees received a training award before their R01 in 2017. Furthermore, the percentage of training awards among the FTR01 awardee population is overrepresented relative to the percentage of training awards among the postdoc population, supporting previous results indicating training awards confer a competitive advantage in attempts to land a faculty position [12,14].…”
Section: Discussionsupporting
confidence: 81%
“…Competition is fierce: nearly 80 percent of newly minted biomedical Ph.D.s enter a postdoctoral research position and more than half of these new postdocs intend to pursue a faculty position, despite this being far more postdocs than there are faculty slots [9][10][11]. Securing an F32 postdoctoral fellowship or a K-series mentored career development award from the National Institutes of Health can increase a candidate's chances of securing a faculty position and future funding, while having high-profile publications can be a predictor of success on the faculty track [12][13][14]. Postdocs also face a series of non-research related obstacles while trying to satisfy research requirements, including relatively low pay, decreased time for families and dimmed earnings prospects [11,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Heggeness et al found that NIH F32 postdoctoral fellowships increased the likelihood of receiving subsequent NIH-funded research awards in general and specifically of receiving subsequent R01 awards ( 4 ). Nikaj and Lund examined the trajectory of researchers who had been awarded K awards during the doubling period of NIH funding (years 1998–2003) and beyond (years 2004–2016) and found that K awardees were 24.1% more likely to obtain an R01, R01 equivalent, or Research Project Grant than researchers without these awards ( 5 ). Similarly, Pickett’s analysis showed that the percentage of investigators obtaining a first-time R01 who previously were awarded F or K awards has steadily increased since 2000 ( 6 ).…”
Section: Why Support Training and Career Development?mentioning
confidence: 99%
“…Competition is fierce: nearly 80 percent of newly minted biomedical Ph.D.s enter a postdoctoral research position and more than half of these new postdocs intend to pursue a faculty position, despite this being far more postdocs than there are faculty slots [911]. Securing an F32 postdoctoral fellowship or a K-series mentored career development award from the National Institutes of Health can increase a candidate’s chances of securing a faculty position and future funding, while having high-profile publications can be a predictor of success on the faculty track [1214]. Postdocs also face a series of non-research related obstacles while trying to satisfy research requirements, including relatively low pay, decreased time for families and dimmed earnings prospects [11, 15].…”
Section: Introductionmentioning
confidence: 99%